Pengaruh Kompetensi,Independensi,Objektivitas,Akuntabilitas Dan Integritas Terhadap Kualitas Audit Dengan Etika Auditor Sebagai Variabel Moderasi (Studi empiris KAP Gafar Salim) - Gita Giyatri; Rahmaita (Jurnal Akuntansi Keuangan dan Bisnis, 2024)
This study aims to examine the effect of competence, independence, objectivity, accountability and integrity on audit quality with auditor ethics as a moderating variable. This study uses a quantitative descriptive approach. The data collection method was carried out by distributing questionnaires. The population in this study were auditors who worked at KAP Gafar Salim. Sampling is obtained from KAP Gafar Salim employees who fill out questionnaires. The results of hypothesis testing show that competence, independence, objectivity, integrity do not have a significant effect on audit quality. While accountability has an influence on audit quality. The interaction of competence and auditor ethics, the interaction of independence and auditor ethics on audit quality has no significant effect. While the interaction of objectivity and auditor ethics, the interaction of accountability and auditor ethics, the interaction of integrity and auditor ethics on audit quality has a significant effect.